THE ALGORITHM OF GOOD PLACEMENT ON THE SHELF BY CONSIDERING THE WEIGHT AND VOLUME OF THE GOODS TO THE CENTRE OF MASS - Ari Setiawan; Leo Rama Kristina; Renaldy Chandra Kurniawan (Center for Study and Journal Management FTI UMI, 2020)
This study aims to develop an algorithm for placing goods on warehouse shelves. The process of placing goods in a warehouse is generally placed or arranged in a rack. Placement of goods must be correct to achieve space efficiency and high shelf utilization while maintaining balance on the storage shelf. The placement of items that have various volumes and weights must consider their placement position on the storage rack. Placing goods carelessly and only consider the shelf utilization rate will cause an imbalance. Shelf imbalance will accelerate the damage to storage racks, as well as the risk of collapsing shelves. Best placement of goods, in order to achieve shelf utilization and maintain shelf balance, must consider the weight and volume of goods placed against the total center mass of the rack. The procedure for placing goods on the shelf by considering the total center of mass was developed from research on warehouse layout. The procedure for placing goods in warehouse layout research is carried out on a two-dimensional plane (x-axis and y-axis). Whereas in this study, the placement of goods was carried out by considering the location of the goods in a three-dimensional plane (x, y and z axes). The placement algorithm is designed to place goods with various size (volume and weight) on multi-layer racks (with assumption each layer has same load capacity). This research produces two placing algorithms. The first algorithm focuses on the weight and volume of goods, so the pallets containing with largest volume and weight goods are arranged first and placed on the lowest layer. The second algorithm focuses on the weight of the goods, the pallets containing the heaviest goods will be arranged first on the lowest layer. Both algorithms are simulated using numerical data. The algorithm that focuses on weight (the second algorithm) has a better mass center than the algorithm that focuses on the weight and volume of goods (the first algorithm).